The artwork’s community - Pioter Shmugliakov (Journal of Aesthetics & Culture, 2020)
The paper explores the inherent political dimension of art, theorized as the artwork’s community: the community structurally constitutive of the work of art as a phenomenon. I distinguish between two major paradigms of the artwork’s community: the Kantian and the Heideggerian. The Kantian is a transcendental aesthetic community, evoked in aesthetic judgment, which thus claims the possibility of emancipated political existence. The Heideggerian, in contrast, is an actual community, sharing the understanding of reality inaugurated by the truth-disclosing event of art. I further distinguish between two possible interpretations of the Heideggerian artwork’s community. The orthodox interpretation conceives of it in terms of Volk, which renders it largely irrelevant for the art of our age. I suggest a new interpretation of the Heideggerian artwork’s community, which keeping with the historical actuality as its essential treat, reduces its scale to the type of community defined by Hakim Bey as temporary autonomous zone (TAZ). I undertake a comparative analysis of two contemporary artistic phenomena, which seem to be informed by an interpretation of the artwork’s community in terms of the latter paradigm: the participatory practices of contemporary art (also known as relational art) and the psytrance dance movement. I show that while psytrance indeed embodies the Heideggerian artwork’s community in its TAZ-version, participatory art operates within the Kantian paradigm, while taking TAZ as the privileged medium of its aesthetic operation.